ANALISIS KRITIS BUKU TEKS BAHASA INDONESIA DALAM KONTEKS KURIKULUM MERDEKA: TINJAUAN TERHADAP KUALITAS DAN RELEVANSI MATERI PEMBELAJARAN - Puan Annisa Pane; Naima Azmi Hutagalung; Mieke Angelika Siburian; Inayah Hanum; Safinatul Hasanah Harahap (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The introduction of the Merdeka Curriculum as the latest innovation in the Indonesian education system marks a paradigmatic change that aims to provide greater opportunities for students to develop their potential holistically. In this context, the quality and relevance of Indonesian language textbooks are crucial in supporting the learning process. This study uses qualitative analysis to evaluate the quality and relevance of Indonesian language textbooks in the Merdeka Curriculum. The results of the analysis show significant differences between evaluation approaches in textbooks from various publishers. In addition, this study highlights the importance of diversity, inclusiveness and relevance of learning materials in textbooks. The findings confirm the importance of in-depth and objective assessment of Indonesian language textbooks to ensure they meet quality and relevance standards in supporting national education goals. With a better understanding of the strengths and weaknesses of the textbooks in use, concrete steps can be taken to improve the quality of student learning and prepare them to face the challenges of an increasingly complex and dynamic world. Keywords: abstract, italic, maximum three words,